ATMOSFER RUANG PADA STUDIO D-ASSOCIATES - Hadini Zaenudin, Nabila; S. Wijayaputri, Caecilia (Jurnal Riset Arsitektur, 2025)
Abstract- The hustle and bustle of Jakarta, the capital city, has resulted in high levels of stress among itsresidents. In 2021, Jakarta ranked 9th in the world as the city with the highest stress levels according to VAAY.Amidst the chaos of Jakarta as a metropolitan city, author who works at d-associates architect, felt that thepresence of their studio seemed detached from the exhaustion often associated with the city's crowded andformal buildings. The dissimilarity in the quality of space atmosphere between the noisy exterior and the calminterior space is evident in the d-associates studio located in the bustling area of Kemang. Based on theaforementioned issues, the research question arises about how do the elements shaping the space atmosphereaffect the emotions of users in the d-associates studio. It is hoped that this research will enhance understandingatmosphere of interior spaces in architecture and their influence on user emotions, as well as cultivate spatialawareness to appreciate architectural spaces in a more systematic and structured manner. This bureau wasfounded by Gregorius Supie Yolodi and Maria Rosantina in 2001, and in 2016, they successfully designed andbuilt their own studio located at Jalan Bangka XI A no. 7B, Kemang, South Jakarta. The initial concept of thisbuilding was to create an informal and flexible office, which is the opposite of the typically rigid and formaloffice typology. This research aims to understand the process of creating the space atmosphere that form in thed-associates studio through these elements, as well as comprehend the influence of the space atmosphere onuser emotions within the studio. The research consists of two stages, the first stage involves collecting physicaldata through observation and photographs to analyze the spatial physicality composed by the architects. Thesecond stage entails collecting mental data by conducting interviews with the architects and distributingquestionnaires to users to assess the perceived atmospheric qualities and their influence on emotions. The spaceatmosphere in the d-associates studio are quite diverse and are experienced in different spaces and times. Theelements shaping the atmosphere, particularly lighting and materials, have a significant influence on the spaceatmosphere and emotions experienced by users in this studio. About 75% of users perceive that the lighting inthe space significantly affects their emotions through the space atmosphere, and 68.8% of users believe that theselected materials have an influence on the space atmosphere and emotions they feel. Satisfaction is the mostcommon emotion experienced in the d-associates studio, with 60% of users experiencing low-intensity positiveemotions. Almost every space is capable of evoking positive emotions in users, except for the architecture studiospace. The architecture studio space shows significant changes in emotions, with positive emotions in themorning and afternoon but negative emotions at night. This is due to inadequate lighting during the nighttime.Therefore, it can be concluded that user emotions are closely related to the perceived atmosphere of the spacethrough sensory perception. An space atmosphere that supports activities will trigger positive emotions, whilean unsuitable atmosphere can lead to negative emotions.Key Words: studio d-associates, space atmosphere, emotion, Kemang Jakarta